**Answer:**

**Option (d) is correct.**

**The equation 5x + 3(x − 1) = 10x − 2x − 3 will have infinite many solution.**

**Step-by-step explanation:**

Given : the equation 5x + 3(x − 1) = 10x − 2x − 3

We have to find the number of solution to the equation 5x + 3(x − 1) = 10x − 2x − 3

Consider the given equation 5x + 3(x − 1) = 10x − 2x − 3

This can be written as two equations as

y=5x + 3(x-1) .........(1)

and y = 10x − 2x − 3 ......(2)

Simplify, both the equations,

y=5x + 3x - 3 = 8x - 3

and y = 10x − 2x − 3 = 8x -3

Since, both equations are same.

So, the graph of both equation will overlap each other.

**Hence, the equation 5x + 3(x − 1) = 10x − 2x − 3 will have infinite many solution.**